Evolution and Intersection of Extended Defects and Stacking Faults in 3C‐SiC Layers on Si (001) Substrates by Molecular Dynamics Simulations: The Forest Dislocation Case. Issue 9 (20th September 2022) - Barbisan, Luca; Scalise, Emilio; Marzegalli, Anna
Abstract : The crossing of stacking faults (namely dislocation forest) in 3C‐SiC has been experimentally probed to cause detrimental effect on the electronic properties of the layer. By means of classical molecular dynamics simulations, Anna Marzegalli and co‐workers (in article number 2100584 ) show for the first time the evolution of two crossing partial dislocation loops, revealing the mechanism that leads to the formation of a complex defect at their intersection.